Sinus Formation as a Manifestation of Chronic Periodontitis In Mandibular Anterior Region: A Report on 2 Cases - Kumari, Anisha; Tewari, Shikha (Journal of Dentistry Indonesia, 2026)
Background: Periodontitis is defined as an inflammatory disease of the supporting tissues of the teeth caused by specific microorganisms, resulting in progressive destruction of the periodontal ligament and alveolar bone. Clinical manifestations of Persistent chronic periodontitis may mimic varied clinical manifestations, including those of apical abscess and systemic involvement. Case report: This report presents the management of an intraoral sinus mimicking a chronic apical abscess in the mandibular anterior region associated with deep periodontal pockets in two male patients in their early thirties. With careful clinical and radiological examination and ruling out of endodontic and systemic involvement, the diagnosis of primary periodontal infection was made. Results: The treatment plan involved initially phase 1 therapy and correction of occlusal discrepancies. After 2 weeks of periodontal surgical intervention that included open flap debridement, both patients reported marked symptomatic improvement, with complete resolution of pain and swelling, and sinus with no recurrence at 3 and 6 months. Conclusions: This case report emphasized careful periodontal examination and diagnosis of primary periodontal infection with intraoral draining sinus mimicking endodontic involvement, which can prevent unnecessary endodontic therapy and tooth extraction.